Research progress in measurement of human accommodative amplitude - LongErping; LinHaotian (眼科学报, 2015)
Accommodation is an important function of the human eye, can change the parameters of ocular refractive system and also has a strong correlation with the development of myopia and presbyopia. Several subjective measurements have been applied in accommodation assessment such as push-up test, push-down test and minus-lens procedures. It can be measured objectively by measuring the change in refraction of the eye with dynamic retinoscopy or autorefractor. This article reviews the application of measurement of accommodative amplitude and research progress in accommodation, providing clinical information for further studies.